Central Venous Access Devices (CVAD) in Pediatric Oncology Patients—A Single-Center Retrospective Study Over More Than 9 Years - Beck, Olaf; Muensterer, Oliver; Hofmann, Sarah; Rossmann, Heidi; Poplawski, Alicia; Faber, Jörg; Gödeke, Jan (Frontiers in Pediatrics, 2019)
Background: Central venous access devices (CVAD) provide important benefits in the management of oncological pediatric patients. However, these catheters are responsible for severe complications. Methods: In this context, we aimed to analyze all patients receiving a CVAD in the Department of Pediatric Hematology and Oncology of the University hospital of Mainz over a period of 9 years, focused on CVAD related complications. Data on demographics, as well as intraoperative and postoperative complications were extracted. Results: A total of 296 patients with a mean age 93.2 ± 62.4 months were analyzed. The majority suffered from leukemia leukemia (n=91, 30.7%), lymphomas (n= 50, 16.9%) and brain tumors (n=48, 16.2%). In 63 (21.3) patients, complications were observed. No death caused by complications of CVADs was found in our series. Catheter-related blood stream infections (BSI) (7.4%) were most prevalent, followed by dislodgements (5.4%), occlusions (2.7%), thrombosis (2.4%) and catheter leakage (2.4%). Insertion site infections were observed in 3 patients (1.0%). Fifty-nine percent of all patients with catheter-related BSI suffered from Leukemia. In patients with Catheter-related BSIs we detected the condition leukemia as the underlying disease as a risk factor compared to solid tumors as the underlying disease. Overall, totally implanted devices (ports) have a lower complication rate than tunneled catheter. Conclusion: Implantation of CVADs seem to be safe and reliable in this large pediatric patient cohort. Even if complications occur in the long-term management of CVADs, they can be treated successfully and long-term catheter survival rates are excellent.